Clinical InvestigationsContrast-enhanced ultrasound as support for prostate brachytherapy treatment planning - Pieters, Bradley; Wijkstra, Hessel; Herk, Marcel van; Kuipers, Ruud; Kaljouw, Emmie; Rosette, Jean de la; Koning, Caro (Journal of Contemporary Brachytherapy, 2012)
Purpose : To investigate the possibility of localization of intraprostatic lesions (IL) with contrast-enhanced ultrasound (CEUS) to support the brachytherapy treatment planning of temporary implants. Material and methods : Two brachytherapy treatment plans were generated for 8 patients treated with external beam radiotherapy and pulsed-dose rate brachytherapy boost for prostate cancer. The first and second brachytherapy treatment plan was without and with knowledge of the localization of the ILs, respectively. Pairwise comparison was performed on prostate, rectum, and urethra dose-volume parameters and total reference air kerma (TRAK)-values. Results : Coverage of the ILs by the 140% isodose was increased from mean 66.0-67.7% for the standard plan to mean 92.5-95.7% for the adapted plan. The mean D90 of the ILs increased from 1.49-1.57 Gy/pulse to 1.76-1.81 Gy/pulse. Dose-volume parameters for the prostate, rectum, and urethra and the TRAK did not change. Conclusions : CEUS technique is a promising method for IL localization to aid in brachytherapy treatment planning. Dose coverage on the IL could be improved without any increase of dose in organs at risk.